Hausdorff dimension of univoque sets - Kallós Gábor (Acta cybernetica, 1999)
In this paper we present the results obtained so far for the determination of the Hausdorff dimension of the univoque set, in number systems with base number greater than 1. The investigation is based on the methods presented in [1] and [2]. We illustrate the theoretical results with interesting examples.